Review on substrate and molybdenum back contact in CIGS thin film solar cell - Ong K.H.; Agileswari R.; Maniscalco B.; Arnou P.; Kumar C.C.; Bowers J.W.; Marsadek M.B. (Hindawi Limited, 2023)
Cadmium telluride; Copper compounds; Deposition; Efficiency; Gallium compounds; II-VI semiconductors; Layered semiconductors; Molybdenum; Molybdenum compounds; Ohmic contacts; Selenium compounds; Solar energy; Solar power generation; Thin film solar cells; Thin films; 'current; Back contact; CIGS; CIGS solar cells; CIGS thin films; Crystalline silicons; Material efficiency; Record efficiencies; Silicon-based; Thin-film technology; Substrates